Response of Sugarcane to Split Application of N and K Under Seedling Cultivation - Lakshmi, M. Bharatha; Srilatha, T.; Ramanamurthy, K. V.; Devi, T. Chitkala; Gouri, V.; Kumari, M. B. G. S. (International Journal of Bio-resource and Stress Management, 2020)
Sugarcane is one of the important agro industrial commercial crops grown in North Coastal Andhra Pradesh, India. Nutrient management play a key role in productivity enhancement of sugarcane. Among the nutrients, sugarcane respond well to split application of nitrogen and potassium especially under seedling cultivation which needs early manuring for fast growth and good tillering. Keeping this in view a field investigation was carried out for two consecutive years during 2016-17 and 2017-18 at Regional Agricultural Research Station, Anakapalle, Andhra Pradesh, India on a sandy loam soil to recommend optimum time of application of nitrogen and potassium for sugarcane raised with single node seedlings. The experiment was laid out in Randomised Block Design with ten treatments consisting of split application of recommended N and K at different crop growth stages and replicated thrice. The experimental results indicated that application of 100% recommended N and K in four splits at planting, 30, 60 and 90 days after planting recorded significantly higher shoot population at 120 DAP, stalk population at 240 DAP and millable cane population at harvest. Higher cane yield (85.4 t ha-1) was recorded with the application of 100% recommended N and K in 4 equal splits at planting, 30, 60 and 90 DAP and proved superior over recommended practice of 100% recommended N at 45 and 90 DAP and entire K at planting (71.5 t ha-1). Quality parameters like brix, sucrose and CCS% were not influenced by split application of N and K significantly.